Biosynthesis and Characterization of Silver Nanoparticles from Marine Seaweed Colpomenia Sinuosa and its Antifungal Efficacy - Dr Vishnu Kiran Manam; Dr Murugesan Subbaiah (International Journal of Pharma and Bio Sciences, 2020)
The present study illustrates the biosynthesis of colloidal silver nanoparticles (AgNPs) from marine seaweed Colpomenia sinuosa and their antifungal efficacy was determined against dermatophytic and non-dermatophytic fungi. The dermatophytic fungi used in this study are Microsporum nanum (ATCC 28951) and Trichophyton mentagrophytes (ATCC 28185) whereas the non dermatophytic fungi Aspergillus flavus (ATCC 20048) and Rhizopus microsporus (ATCC 22960). The rich content of phytochemicals, bioactive compounds and secondary metabolites in marine seaweed Colpomenia sinuosa possess the reducing/capping agents that may be environmentally acceptable and eco-friendly for the biosynthesis of silver nanoparticles. The efficacy of biosynthesized silver nanoparticles from marine macroscopic brown alga was performed using Kirby Bauer Method and the silver nanoparticles biosynthesized was characterized by UV-vis spectroscopy, Fourier Transform Infrared (FTIR) Spectroscopy, X-ray Diffraction (XRD) and Thermo gravimetric analysis. Particle size distribution and morphology were investigated by scanning electron microscope which showed silver nanoparticles in the size range of 54-85 nm. The average size of the silver nanoparticle indicated by TEM analysis was found to be 34 nm. The antifungal efficacy of silver nanoparticles at the concentration 30 µg/mL revealed greater efficacy in dermatophytic fungi while Rhizopus microsporus as non dermatophytic fungus showed better antifungal activity when compared to the standard fungal antibiotics used.